Approaching urban vulnerability to climate change induced risks in socio-environmentally fragmented areas: The case of Santiago de Chile - Kerstin Krellenberg; Felipe Link; Juliane Welz; Katrin Barth; Jordan Harris; Felipe Irarrázaval; Felipe Valenzuela (Helmholtz-Zentrum für Umweltforschung (UFZ), 2015)
[Foreword ...] The present report contains the results of the initial working steps of the CLAVE project which is a) the theoretical combination of fragmentation and vulnerability, and b) the development of a methodology for assessing socio-environmental fragmentation and residential vulnerability in order to enhance the overall knowledge of urban vulnerability. This is seen as the primary prerequisite for the subsequent elaboration and implementation of local adaptation measures. The different methodological steps and in-depth analyses to be undertaken are described by using selected municipalities within the MAS. Chapter 2 focuses on describing the underlying problem of linking the theoretical approaches of fragmentation and vulnerability from a general point of view. Existing approaches presented by other authors are discussed, in order to link as well as distinguish the work presented here with/from others. Chapter 3 shows how the concepts of fragmentation and vulnerability are interlinked from the project's point of view. Chapter 4 describes the theoretical background of climate change adaptation and adaptive capacity in order to allow a better understanding of both the CLAVE project approach and its application. The case study, the MAS, is described and illustrated in Chapter 5 by providing a general overview of the city together with existing findings with regard to fragmentation and vulnerability. This chapter thereby explains the context in which the approach is to be applied. Chapter 6 presents the project's methodological framework with its three-stage approach as an integrated assessment of urban vulnerability to climate change. Options for validating the approach are likewise discussed. Chapter 7 summarizes the main conclusions and provides an outlook by describing success stories and lessons learned for validating the theoretical approach. The development of strategies to deal with future climate change in these and other regions worldwide is discussed.
Keywords: 330